Analysis of Pre and Post Merger and Acquisition Financial Performance of Banks in Pakistan - Abbas, Qamar; ., Rashid Saeed; ., Ehsan-Ul-Hassan; ., Muhammad Shahzad Ijaz (Information Management and Business Review, 2014)
Merger and Acquisition is a strategy adopted by the organizations globally to meet the needs of dynamic business environment. This strategy also has much importance in Pakistan mostly in banking sector. Therefore, the objective of the study is to assess the impact of M&A on the financial performance of banks in Pakistan. The accounting and financial data of 10 banks were used in this study. Data was taken from the financial statement analysis (FSA) by State Bank of Pakistan from the period of 20062011. For the analysis of pre and post Merger and Acquisition performance 15 financial ratios were used in the study. To compare the results Paired sample t-Test was used to measure the significant difference between pre and post M&A financial performance. The overall results show that there is no significant difference in financial performance. It is concluded that there is insignificant difference between pre and post M&A performance of banks in Pakistan.